Analisis Model Mental Peserta Didik pada Pembelajaran Sistem Periodik Unsur Menggunakan Represnetasi 3D - Noviyanti, Rezti Wahyu; Rahmawati, Yuli; Pratiwi, Yussi (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the mental model of students in learning the periodic system of elements using 3D representations. This research was conducted in the odd semester of the 2022/2023 academic year. The research subjects were 36 students of class XB SMAN 54 Jakarta. This study used qualitative research methods. Data collection techniques through mental model tests, interviews, reflective journals, and classroom observations. The students' mental models were analyzed in three stages, namely engage, explore, and explain. The students' mental models are categorized into three, namely scientific, synthetic, and initial mental models which are viewed from the three levels of macroscopic, submicroscopic, and symbolic representations. The results showed that class XB had three categories of mental models, namely scientific mental models with an overall average of 70.86%, synthetic mental models with an overall average of 17.54%, and initial mental models with an overall average of 11.60 %. Mental models are formed from the thoughts and experiences of students who previously had, teacher explanations, 3D representation media, and handbooks or other sources.